Impacts of the 4th East Asian games on residents’ participation in leisure sports and physical activities – the case of Macau, China - Li, Yiping; Luk, Yim Mei (Acta geographica Slovenica, 2011)
Sport events and the associated impacts are not new subjects for academic research, and the past enquiries have given substantial attentions to the economic impacts, especially those of tourism. Some important social issues have not been sufficiently investigated, including the extent to which sport events stimulate resident interest in leisure sports and the enhancement effects on public health. This study aims to address the past omissions through an examination of the 4th East Asian Games. It especially focuses on the extent to which the event stimulated resident participation in leisure sports and physical activities, so as to draw implications for public health enhancement and the ripple benefits for tourism. Combined methods were used for the investigation, which included questionnaire survey, in-depth interviews, documentary research and on-site observations. The results indicate that respondents who were highly attached to the sport promotion schemes of the event perceived most positive impacts and were more likely to support the city to host similar events in the future. While the results show to a certain extent that the 4th East Asian Games stimulated resident interest in leisure sports, forming and adopting relevant policies are considered necessary for nurturing a community culture of sports that may help construct a public health image of the host city and, this will eventually benefit local tourism.